Literatura migrante na França: a premiação de Chanson Douce, de Leïla Slimani, e de Petit Pays, de Gaël Faye, pela Academia Goncourt - Meireles, João Ricardo da Silva (2021)
This thesis analyzes the historical constitution of France and how its people see themselves and see internal and external migratory movements, especially the French vision of migration coming from underdeveloped African and Asian countries, many of them former colonies of exploitation of the French empire. This analysis starts from the questioning about what it is to be French and what are the historical and political criteria that guarantee that something or someone becomes French. It also analyzes the constitution and importance of literary prizes for the French and French-speaking reading community. Among the literary awards and academies, the Goncourt Academy stands out, a century-old institution responsible for annually moving hundreds of bookstores, publishers, writers, professors, journalists, politicians and readers around the autumn awards. In 2106, the most outstanding awards went to two young writers, Leïla Slimani and Gaël Faye. Slimani, a Maghreb writer from Morocco, received the Goncourt Grand Prize for her work Chanson Douce (2016), which portrays the life of the small French middle class of the Massé, who hire a traditional French nanny who, after winning the affection of the family, murders the children. two children she takes care of. With a third-person narrative, the work examines the family's daily life and how structural racial prejudice influenced the decisions of the Massé couple and how the other nannies in the neighborhood, mostly immigrants, related to each other. Faye, winner of the Goncourt Prize for French High School Students, receives the award for her first book Petit Pays (2016). A self-fictional work, it has the look of the narrator Gabriel, who narrates the events that preceded the Tutsi massacre in Rwanda with lightness and with the purity of the child's gaze. The massacre was recognized as genocide months after its beginning, in 1994. To analyze the importance and history of the awards, the extensive work of Sylvie Ducas (2010, 2013, 2019). To analyze the migrant literature in its various contexts, the studies of professor Oana Sabo (2018) will be used. To present a panoramic view of the migratory history in France and the concepts involving migration in all its facets, the works of Elen Declerq (2011), Bruno Dumézil (2017) and Priscila Fergusson (1991) will be used. Other theorists and scholars will also be added to the work.